DESAIN SISTEM INFORMASI AKUNTANSI ASET PADA DINAS PERINDUSTRIAN DAN TENAGA KERJA, KOTA SALATIGA - Ulfa Idayati; Evi Maria; Christ Rudianto (Monex: Journal of Accounting Research, 2022)
The purpose of this research is to design an asset accounting information system at the Departement of Industry and Labor, Salatiga City. This research focuses on designing systems ranging from demand activities, procurement and asset procurement decisions, depreciation and calculation of asset depreciation, asset removal, monitoring, recording and reporting of assets. This research uses prototype methods with codeIgneter framework and MySQL database in the development of asset accounting information system. This research resulted in the design of asset accounting information system to be implemented at the Departement of Industry and Labor, Salatiga City. The results of system testing show that the design of the asset accounting information system generated in this research can produce valid asset reports, on time, and free from errors. The results of this research are expected to provide solutions to the problems of state asset management related to the accuracy of the report and the time of presentation of asset reports.